Self-actors between spatial connotation of power and succession Gall act - لعيبي هادي عبد الحسن (Al-Adab Journal, 2019)
The study reveals The intimate Link in flaenes of the an thority of the place and do storytelling by and between self – actors of the last of those valeting to that form in side paper poetic text cross product approaches and comparisons represent the place and the diversity of its forms, which ravied for the pool in seventh abayll act of self Gaove lsvh and visions cultural and depth of experience and accuracy out look to the place overtaking add to their wording and expressions in details the phenomenon of surface features and the adoption of insight vttakty the limits of Article natural attributes and set dimensions and reveal A anthialata of the nature of The relationship between them through. The act of storytelling does not become poetic only but a presence creative beyond the limits of Article. Paints for our self – image that come out of feelings on the place to be pirt of the essence of the decree and then be recorded creative presence of the text and flying from his cove.